AN ANALYSIS OF FLOUTING MAXIM IN "OZ THE GREAT AND POWERFUL FILM" - Nenni Triana Sinaga; Fitri Yuneza Lumban Gaol; Lastri Wahyuni Manurung (Jurnal Scientia, 2023)
The purpose of this research is to examine the use of flout maxims in various situations and to determine which situations a character in the movie "Oz the Great and Powerful" out the maxims. The data were analyzed using a qualitative descriptive technique based on Grice's maxims and the principle of cooperation. The research data was derived from the conversations of the film's major characters, Theodora and Oscar Diggs, with the film's dialogue serving as the research context. Scripts films serve as study data sources. Thus, there are four types of flouting of the maxims committed by the characters in the film. The maxim of quantity is violated by providing incorrect and unnecessary information, the maxim of quality is violated by providing false information, the maxim of relation is violated which is irrelevant, and the maxim of manner is violated by providing information that is not clear. The finding of this research, four types of maxims are violated: 10 utterances violate the quantity maxim, 1 utterance violates the quality maxim, 1 utterance violates the relation maxim, and 1 utterance violates the manner maxim. Based on the research on the maxims flouted, this study concludes utterance that maxims are still flouted in films. It is necessary to fulfill four types of maxims in order to have a cooperative and effective discourse.